Performance Leadership in the Digital Era: Transforming Strategies for Sustainable Organization Excellence in Higher Education Institutions - Teti Rohayati (AL-ISHLAH: Jurnal Pendidikan, 2025)
Digital technologies are reshaping how higher education institutions (HEIs) deliver learning, manage research, and run core services, yet many digital initiatives fail to translate into sustained organizational excellence. Leadership is a critical determinant of whether digital transformation becomes a strategic, mission-aligned change rather than fragmented technology adoption. This study develops an integrative conceptual account of performance leadership as a core enabling mechanism for HEI digital transformation. Using an integrative review guided by PRISMA-oriented selection and thematic synthesis, the study examines recent scholarship (2014–2024) on leadership, digital transformation, governance, and performance management in HEIs. The synthesis identifies four recurring dimensions of effective performance leadership: (1) digital literacy and technological competence, (2) agile and adaptive management, (3) stakeholder-centric governance, and (4) performance analytics and data-driven accountability. Building on these themes, the study proposes a conceptual model in which performance leadership strengthens digital transformation outcomes through mediating mechanisms such as strategic execution quality, performance-driven culture, and data governance maturity, while recognizing contextual moderators (e.g., institutional digital maturity, governance structures, and regulatory pressures). The article contributes a higher-education-specific framework and a set of testable propositions to guide future empirical research. Practically, it offers actionable implications for HEIs on leadership development, participatory governance, and responsible analytics use to support sustainable outcomes in teaching quality, innovation, and operational efficiency.